Posterior Fossa Tumors in Infants: 13-year single center retrospective review. - Natália Dassi; Carolina Silva de Aguiar; Patricia Dastoli; Nasjla S Silva; Sergio Cavalheiro; Andrea M Cappellano (Brazilian Society for Pediatric Neurosurgery, 2023)
Introduction/Background: Central nervous system (CNS) tumors in infants are rare, ranging between 1 and 10% of all pediatric CNS tumors. The infratentorial location is a challenge to neuro-oncologist and -surgeons due their subtle clinical presentation, different histopathological types, biological behaviors, and anesthetic-surgery difficulties. Methods: Single center retrospective study of infants diagnosed with posterior fossa tumors between 2010 and 2023. Results: Nineteen patients were included. Mean age 8.8 months; eight males. The most common presenting symptom was torticollis (n-6, 31.6%), followed by vomiting (n-3, 15.8%) and increased head circumference (n-3, 15.8%). Atypical Teratoid Rhabdoid Tumor (AT/RT) was the most common subtype (n-11, 57.9%), followed by Medulloblastoma (MB). Metastatic disease at diagnosis was evident in five cases. Seventeen patients initially underwent correction of hydrocephalus. Regarding surgical resection, one (5.3%) patient underwent biopsy, 13 (68.4%) complete resection, four (21%) partial resection. Only one patient, diagnosed with ependymoma, did not receive chemotherapy after surgery, 14/19 received high-dose chemotherapy, eight of these followed by autologous bone marrow transplantation (ABMT). Focal radiotherapy (RT) was performed in four patients with AT/RT and in one ependymoma, following ABMT and complete resection, respectively. Event-free survival at 2 and 5 years was 64.9% and overall survival 63.2% and 54.2% respectively. Conclusion: Despite aggressive histological subtypes, neurosurgical challenges, and limitation of adjuvant therapy, we have shown acceptable survival rates in this challenging group of patients showing the importance of appropriate supportive care, improvement in surgical techniques and a multi-professional approach.